2020
DOI: 10.1111/ecog.04888
|View full text |Cite
|
Sign up to set email alerts
|

Forest and connectivity loss drive changes in movement behavior of bird species

Abstract: In a rapidly changing world, it is important to understand how environmental modifications by humans affect species behavior. This is not a simple task, since we need to deal with a multitude of species and the different external contexts that affect their behavior. Here, we investigate how interpatch short‐distance movements of 73 common forest bird species can be predicted by forest cover and forest isolation. We modeled bird movement as a function of environmental covariates, species traits – body mass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Cedrela, Ceiba), seed dispersal in wet tropical forests is overwhelmingly driven by animals (Gentry 1982). Animal movement patterns are impacted by forest fragmentation and loss, which can either increase or decrease their range depending on the species and study system in question (Nield et al 2020, Ramos et al 2020. Movement is also driven both by landscape configuration and connectivity (Lehouck et al 2009a, Kormann et al 2016, Cadavid-Florez et al 2019, as well as by resource availability such as the provision of fleshy fruit (Lehouck et al 2009b, Camargo et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Cedrela, Ceiba), seed dispersal in wet tropical forests is overwhelmingly driven by animals (Gentry 1982). Animal movement patterns are impacted by forest fragmentation and loss, which can either increase or decrease their range depending on the species and study system in question (Nield et al 2020, Ramos et al 2020. Movement is also driven both by landscape configuration and connectivity (Lehouck et al 2009a, Kormann et al 2016, Cadavid-Florez et al 2019, as well as by resource availability such as the provision of fleshy fruit (Lehouck et al 2009b, Camargo et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In most landscapes, the open non-forested areas did not present itself as a barrier for the high-mobility seed dispersers movement, which are large body birds, however, it was a limitation for low-mobility seed dispersers (smaller birds) and particularly for pollen dispersers insects). This result was expected since large-bodied species, may exhibit higher movement capacity (Spiegel and Nathan, 2007;Neuschulz et al, 2013;Ramos et al, 2020) and, to ensure sufficient resources, should be more likely to change their behavior in response to variation in resource distribution than small-bodied species (Buchmann et al, 2012;Ramos et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The SLEs contribute to connect the fragments and increase genetic flow. Also, the connectivity provided by the SLEs can be very important to the landscape resilience, since birds can change they movement according to the level of landscape isolation (Giubbina et al, 2018), by using stepping-stones, using more pasture or moving farther (Ramos et al, 2020). Consider the example of the scattered trees in pastures, where Siqueira et al (2017) observed a much larger deposition of animal dispersed seeds under scattered trees than in corresponding areas without the trees.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat connectivity has been proven to have a significant influence on biodiversity [85]. For birds, of which survival, reproduction, and activities are highly sensitive to the movements of matter and energy, variations in their populations can be easily affected by the connectivity among habitat patches [43,86,87]. As shown in Figure 9, there was a significant association between HQCI and bird species richness according to Fisher's exact test.…”
Section: Applicability Of the New Combined Indicator Of Habitat Quality And Connectivity In Explaining Bird Diversitymentioning
confidence: 93%